2003
DOI: 10.1167/iovs.03-0240
|View full text |Cite
|
Sign up to set email alerts
|

Pinin/DRS/memA Interacts with SRp75, SRm300 and SRrp130 in Corneal Epithelial Cells

Abstract: The results suggest that Pnn and SR-rich proteins may be part of a multiprotein complex within the nucleus and may be involved in pre-mRNA processing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
54
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 40 publications
0
54
0
Order By: Relevance
“…Furthermore, ␤-catenin has been recently reported to influence pre-mRNA splicing (Sato et al, 2005;Lee et al, 2006), a process where PNN is also involved (Li et al, 2003;Zimowska et al, 2003). Even though the relevance of these functional commonalities needs further investigation, our in vivo studies may provide a crucial insight into PNN's connection to a signaling pathway, which may govern biological processes in which PNN has been shown to be involved.…”
Section: Discussionmentioning
confidence: 82%
See 2 more Smart Citations
“…Furthermore, ␤-catenin has been recently reported to influence pre-mRNA splicing (Sato et al, 2005;Lee et al, 2006), a process where PNN is also involved (Li et al, 2003;Zimowska et al, 2003). Even though the relevance of these functional commonalities needs further investigation, our in vivo studies may provide a crucial insight into PNN's connection to a signaling pathway, which may govern biological processes in which PNN has been shown to be involved.…”
Section: Discussionmentioning
confidence: 82%
“…Pinin, a nuclear and desmosome-associated protein, has been shown to play multiple roles in intercellular adhesion, tumor suppression, transcriptional regulation, and pre-mRNA splicing (Shi et al, 2001;Zimowska et al, 2003;Alpatov et al, 2004;Joo et al, 2005). Prior in vitro studies demonstrated that PNN overexpression results in the enhanced epithelial phenotype characterized by increased cell-cell adhesion and decreased motility (Ouyang and Sugrue, 1996;Shi et al, 2000bShi et al, , 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Its roles include regulation of alternative splicing, mRNA export, and transcriptional activity regulation (Wang et al, 2002;Li et al, 2003;Alpatov et al, 2004). Yeast two-hybrid assay and co-immunoprecipitation experiments demonstrated that Pnn interacts with several splicing-related SR family proteins, including SRp75, SRm300, SRp130, SRcyclophilin and RNPS1 and binds preferentially to splicedmRNA (Li et al, 2003;Lin et al, 2004;Zimowska et al, 2003). Apart from its roles within the nucleus, Pnn has also been shown to be involved in other cellular functions including the enhancement of cell-cell adhesion (Ouyang and Sugrue, 1996) and corneal cell migration (Shi et al, 2000b).…”
Section: Introductionmentioning
confidence: 99%
“…SR proteins distinguished by their serine/argininerich motifs are required for constitutive mRNA splicing and regulation of alternative splice site selection (6,30,36,37,47,58). Previous two-hybrid and colocalization experiments revealed that Pnn indeed binds to, and colocalizes with, the SR protein family members SRp75 and SRm300, known components of the spliceosome machinery, and a novel SR protein (9,47,62,65). In addition, Pnn was demonstrated to contribute to the alternative splice site selection in splicing reporter assays, specifically the regulation of 5Ј splice site choice (62).…”
mentioning
confidence: 99%